(untitled) (Seminar_BG, 2025)
The article examines urban cycling not only as a means of transportation, but also as an embodied experience that unfolds in the communication between the cyclist as a body, the bicycle as a device, and the urban infrastructure as a place and landscape. Using an autoethnographic approach, the article analyzes three group cycling events in Sofia, Cagliari, and Vienna to reveal the diverse social, cultural, and aesthetic dimensions of cycling. The study begins with a review of the academic literature on cycling and its significance in the context of sustainable urban development. The methodology and scope of the field study are then presented. The main analysis includes three cases: the “Sofia green tour,” a tourist cycling tour in Sofia viewed from the perspective of a tour guide; the “Critical Mass” protest march in Cagliari as a form of civic activism; and the “Spiral bike” bicycle concert with electronic music in Vienna as an example of creative use of urban space. In conclusion, the article synthesizes the main conclusions and offers guidelines for improving urban cycling infrastructure, addressing both local authorities and active cyclists. References Chang, Heewon. 2008. “Chapter 3: Autoethography”. in: Autoethography as method. Walnut Creek: CA: Left coast press, 43-57. De Certeau, Michel. 1984. The practice of everyday life. London: University of California press. Dichev, Ivaylo. 2019. Kulturni stseni na politicheskoto. Sofia: „Prosveta-Sofia“ AD. Dichev, Ivaylo. 2017. „Zashto v Sofia ne e hubavo“, DW Obshtestvo, 11.10.2017, https://www.dw.com/bg/%D0%B7%D0%B0%D1%89%D0%BE-%D0%B2-%D1%81%D0%BE%D1%84%D0%B8%D1%8F-%D0%BD%D0%B5-%D0%B5-%D1%85%D1%83%D0%B1%D0%B0%D0%B2%D0%BE/a-40902347 [last seen 28.06.2025] Dunlap, Rudy, Rose, Jeff, Standridge, Sarah H., Pruitt, Courney L. 2020. “Experiences of urban cycling: emotional geographies of people and place”. Leisure Studies, DOI: 10.1080/02614367.2020.1720787 Fincham, Ben. 2007. “Bicycle messengers: image, identity and community”. In: Horton, Dave, Rosen, Paul and Cox, Peter (eds.) Cycling and Society. Cornwall: Ashgate, 179-198. Green, Judith, Steinbach Rebecca and Datta, Jessica. 2012. “The Travelling Citizen: Emergent Discourses of Moral Mobility in a Study of Cycling in London”. Sociology, 2012 46: 272-289, DOI: 10.1177/0038038511419193. Hajimichael, Mike. 2016. "Politseyskata aktsia sreshtu „Okupiray“ v Kipar: avtoetnografia varhu „Za 1 gram“". Balgarska etnologia, 1: 71-83. Horton, Dave, Rosen, Paul and Cox, Peter (eds.). 2007. Cycling and Society. Cornwall: Ashgate. Jones, Phil. 2005. “Performing the city: a body and a bicycle take on Birmingham, UK”. SOCIAL AND CULTURAL GEOGRAPHY 6;4, 2005: 813-830. Lorimer, Hayden. 2011. “Walking: New Forms and Spaces for Studies of Pedestrianism”. In: Cresswell, Tim and Merriman, Peter (eds.) Geographies of Mobilities: practices, spaces, subjects. UK: Ashgate, 19-34. Rana, Pranaya. 2018. Walking In The City Self And Spatiality In Copenhagen And Kathmandu, MA, https://www.4cities.eu/wp-content/uploads/2018/10/RANA_Master-Thesis.pdf [last seen 20.01.2025]. Simpson, Clare. 2005. “Capitalising on curiosity: Woman’s professional cycle racing in the late-nineteenth century”. In: Horton, Dave, Rosen, Paul and Cox, Peter (eds.) Cycling and Society. Cornwall: Ashgate, 47-66. Sofia Green tour, 2025, https://sofiagreentour.com/ , [last seen 20.01.2025] RAD Performance, 2025, https://radperformance.at/en/home-en/ , [last seen 20.01.2025] Spinney, Justin. 2007. “Cycling in the city: non-place and the sensory construction of meaning in a mobile practice”. In: Horton, Dave, Rosen, Paul and Cox, Peter (eds.) Cycling and Society. Cornwall: Ashgate, 25-46. Strathern, Marilyn. 1987. “The limits of autoethography”. In: Jackson, Anthony (ed.) Anthropology at home. New York: Tavistock, 16-37. Wall, Sarah. 2008. “Easier Said than Done: Writing an Autoethnography”. International Journal of Qualitative Methods, 2008, 7(1): 38-53.